Back to the future? The long view of probation and sentencing: a practitioner response - Shepherd, Becky (Probation journal, 2019)
This practitioner response reflects on Peter Raynor’s insights into the role probation has played in sentencing over several decades. It considers some current challenges for probation staff in court, including speedy justice initiatives and the changing role of reports. This article conceptualises current probation practice within a continuum of person-centred practice which, although modernised, is informed by the traditional probation principles of advise, assist, and befriend.